Hormone-Like Effects of 4-Vinylcyclohexene Diepoxide on Follicular Development - Cao, Lian Bao; Liu, Hong Bin; Lu, Gang; Lv, Yue; Leung, Chi Kwan; Du, Yan Zhi; Wang, Wu Ming; Xiong, Zhi Qiang; Su, Xian Wei; Li, Hong Jian; Chen, Zi-Jiang; Ma, Jin Long; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background 4-vinylcyclohexene diepoxide (VCD) has long been considered a hazardous occupational chemical that promotes ovarian failure. However, VCD is also used as a research compound to chemically induce animal models of premature ovarian insufficiency (POI), and in related work we unexpectedly found that VCD apparently exhibits both dose- and duration-dependent opposing, hormone-like effects on the maintenance of the primordial follicle pool, follicle development, and ovulation induction. Results We conducted experiments with cultured murine ovaries and performed transplantation experiments using postnatal day (PD) 2 and PD12 mice and found that low-dose, short-term exposure to VCD (VCDlow) actually protects the primordial/primary follicle pool and improves the functional ovarian reserve (FOR) by disrupting follicular atresia. VCDlow inhibits follicular apoptosis and regulates the Pten-PI3K-Foxo3a pathway. Short-term VCD exposure in vivo (80 mg/kg, 5 days) significantly increases the number of superovulated metaphase II oocytes, preovulatory follicles, and corpus luteum in middle-aged mice with diminished ovarian reserve (DOR). We demonstrate that low-dose but not high-dose VCD promotes aromatase levels in granulosa cells (GCs), thereby enhancing the levels of estradiol secretion. Conclusion Our study illustrates a previously unappreciated, hormone-like action for the occupational “ovotoxin” molecule VCD and strongly suggests that VCDlow should be explored for its potential utility for treating human ovarian follicular development disorders, including subfertility in perimenopausal women.